Quality of basic maternal care functions in health facilities of five African countries: an analysis of national health system surveys - Dr. Margaret E Kruk, MD; Hannah H Leslie, PhD; Stéphane Verguet, PhD; Godfrey M Mbaruku, MD; Richard M K Adanu, MBChB; Ana Langer, MD (Elsevier, 2016)
Background: Global efforts to increase births at health-care facilities might not reduce maternal or newborn mortality if quality of care is insufficient. However, little systematic evidence exists for the quality at health facilities caring for women and newborn babies in low-income countries. We analysed the quality of basic maternal care functions and its association with volume of deliveries and surgical capacity in health-care facilities in five sub-Saharan African countries. Methods: In this analysis, we combined nationally representative health system surveys (Service Provision Assessments by the Demographic and Health Survery Programme) with data for volume of deliveries and quality of delivery care from Kenya, Namibia, Rwanda, Tanzania, and Uganda. We measured the quality of basic maternal care functions in delivery facilities using an index of 12 indicators of structure and processes of care, including infrastructure and use of evidence-based routine and emergency care interventions. We regressed the quality index on volume of births and confounders (public or privately managed, availability of antiretroviral therapy services, availability of skilled staffing, and country) stratified by facility type: primary (no caesarean capacity) or secondary (has caesarean capacity) care facilities. The Harvard University Human Research Protection Program approved this analysis as exempt from human subjects review. Findings: The national surveys were completed between April, 2006, and May, 2010. Our sample consisted of 1715 (93%) of 1842 health-care facilities that provided normal delivery service, after exclusion of facilities with missing (n=126) or invalid (n=1) data. 1511 (88%) study facilities (site of 276 965 [44%] of 622 864 facility births) did not have caesarean section capacity (primary care facilities). Quality of basic maternal care functions was substantially lower in primary (index score 0·38) than secondary care facilities (0·77). Low delivery volume was consistently associated with poor quality, with differences in quality between the lowest versus highest volume facilities of −0·22 (95% CI −0·26 to −0·19) in primary care facilities and −0·17 (−0·21 to −0·11) in secondary care facilities. Interpretation: More than 40% of facility deliveries in these five African countries occurred in primary care facilities, which scored poorly on basic measures of maternal care quality. Facilities with caesarean section capacity, particularly those with birth volumes higher than 500 per year, had higher scores for maternal care quality. Low-income and middle-income countries should systematically assess and improve the quality of delivery care in health facilities to accelerate reduction of maternal and newborn deaths. Funding: None.